2010
DOI: 10.1111/j.1476-4431.2010.00544.x
|View full text |Cite
|
Sign up to set email alerts
|

Case Series: Continuous electroencephalographic monitoring of status epilepticus in dogs and cats: 10 patients (2004–2005)

Abstract: Continuous EEG monitoring appears to be a useful tool for therapeutic monitoring of SE in dogs and cats. It allows the detection of EEG seizures without the appearance of clinical seizures. Further investigations with blinded investigators and homogeneous animal groups to define therapeutic endpoints are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 58 publications
(76 reference statements)
1
31
0
Order By: Relevance
“…Continuous intensive care unit (ICU) EEG monitoring is routinely done for human SE patients. Similar monitoring for NCSE has been done in some canine and feline patients and proposed to be further investigated, 6 but it is not standard practice in veterinary ICUs at this time.…”
Section: Convulsive Status Epilepticusmentioning
confidence: 87%
See 1 more Smart Citation
“…Continuous intensive care unit (ICU) EEG monitoring is routinely done for human SE patients. Similar monitoring for NCSE has been done in some canine and feline patients and proposed to be further investigated, 6 but it is not standard practice in veterinary ICUs at this time.…”
Section: Convulsive Status Epilepticusmentioning
confidence: 87%
“…13 Resulting autonomic and endocrine dysfunction can lead to loss of normal brain homeostasis, kindling, functional and structural hippocampal changes, neurodegeneration, and altered distribution of ion channels and neurotransmitter receptors on a cellular level. 6 Systemically, prolonged or frequent seizures can result in hyperglycemia, hypertension 11 neuronal necrosis, hyperthermia, cardiac arrhythmias, kidney damage, metabolic acidosis, disseminated intravascular coagulation, cardiorespiratory failure, and a predisposition to further seizure episodes. 4 Consequently, aggressive and safe early intervention is important.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed electroencephalographic evidence of seizure activity in the brains of dogs in status epilepticus even after their clinical seizure activity was stopped . Nonconvulsive status epilepticus can increase excitotoxic neuronal damage in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…The role of an urgent EEG in an unresponsive patient is somewhat limited, with the exception of nonconvulsive status epilepticus. 29,30 Nonconvulsive status epilepticus should be suspected in any patient with a history of seizures that becomes acutely unresponsive, but also can be considered in otherwise unexplained cases of acute unresponsiveness. 17,29 Fig.…”
Section: Electrodiagnostic Evaluationmentioning
confidence: 99%